Performa dan Kualitas Karkas Ayam Broiler Yang Diberikan Jus Daun Pepaya (Carica papaya L) Dengan Level dan Frekuensi Yang Berbeda - Alam, Nur; Hidayat, Muhammad Nur; Jamili, Muhammad Arsan (Anoa: Journal of Animal Husbandry, 2024)
This study aims to determine the performance and carcass quality of broiler chickens given papaya leaf juice at different levels and frequencies. This research was conducted for 42 days in 35 days of treatment from 8 May to 18 June 2022. The location for the research was Tuppu Village, Kec. Lembang, Kab. Pinrang, South Sulawesi. This study used a completely randomized design consisting of 3 treatments and 3 replications. This study used doses of P1 (20 ml/liter papaya leaf juice 1 time/week), P2 (20 ml/liter papaya leaf juice 2 times/week), and P3 (20 ml/liter papaya leaf juice 3 times/week). . Parameters measured were feed consumption, body weight gain, feed conversion, and carcass percentage. The results showed that giving papaya leaf juice in drinking water had a significant effect on feed consumption in treatment P1 (886.83 g/head) and had no significant effect on body weight gain in treatment P2 (412.93 g/head), feed conversion P1 (2.17 g). /head) and Percentage of Carcass P3 (79.05 %).